ACL rupture in the immediate build-up to the Olympic Games: return to elite alpine ski competition 5 months after injury and ACL repair. Issue 3 (15th March 2019) - Praz, Cesar; Kandhari, Vikram Kishor; Saithna, Adnan; Sonnery-Cottet, Bertrand
Abstract : Anterior cruciate ligament (ACL) rupture in the immediate build-up to a major international competition can preclude an athletes' participation due to the prolonged period of rehabilitation that is typically required after ACL reconstruction. ACL repair is an alternative strategy that has been postulated to confer the advantage of rapid rehabilitation and earlier return to sport. A 33-year-old professional alpine skier sustained a right knee ACL rupture in September 2017. The athlete indicated that she wanted to participate in the 2018 Olympics. Arthroscopic ACL repair and reconstruction of the anterolateral ligament was undertaken. At 3 months, Lachman's test revealed a hard end point, a negative pivot shift and no side-to-side laxity difference. MRI at 6 and 12 weeks demonstrated a continuous ACL with no intraligament signal change. At 20 weeks postoperatively, she successfully participated in the slalom at the 2018 Olympic Games.